Questionnaire to assess the significance of history taking in assessment of otitis media with effusion in children - AlQaed, Reem Mohamed; Salman, Ayman; Aljawder, Salman Mohamed; Riskalla, Andrew Nabil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: There is a high prevalence of Otitis media with effusion (OME) with diagnoses of least 50% of children under the age of one, and 60% of children under the age of two. Complications have a significant impact on a child’s quality of life including hearing impairment, language acquisition delay, declining school performance, and behavioral problems. The objective of the study is to develop and test the reliability of a simple questionnaire based on common complaints given by caregivers of children with OME. Methods: 100 patients were included from the ENT Clinic at King Hamad University Hospital and categorized into preschool age (1-4 years) and School age (5-15 years). A bilingual binary questionnaire was developed (Cronbach’s Alpha: 0.89). Results: There were 22 preschool age patients, and 78 school age patients. Six complaints were significant where the child does not respond to name calling (p=0.031), needs to raise the TV volume (p=0.000), occasionally talks loudly (p=0.003), uses verbal communication for their needs (p=0.000), has episodes of clumsiness and dizziness (p=0.000), and doesn’t pronounce words correctly according to their age (p=0.008). Conclusions: Questionnaires based on complaints can aid the diagnosis of OME as caregiver’s assessment is often limited.